Integration of knowledge in organic chemistry: a contribution in the training of pharmaceutical professionals - Guerra-Ortiz, Mayda Esther (Revista Cubana de Química, 2022)
The objective of the work presented is the implementation of a system of exercises and seminars that contribute to the integration of knowledge in Organic Pharmaceutical Chemistry for students of the first and second years of the Pharmaceutical Sciences career of the Universidad de Oriente, which allows them to become familiar with the resolution of problems related to their profession. Theoretical and empirical methods were applied in the research. The study was carried out from the 2019-2020 to 2021-2022 academic year. The results obtained demonstrated the need to continue with the systematization of this type of teaching activities, not only to achieve a greater acquisition of knowledge, but also integration and motivation on the part of the students. The implementation of this system of actions contributed to the integration of knowledge within the Organic Chemistry discipline itself and that contribute to subjects that the students will later receive in the career.